Those Who Know Most: Insider Trading in Eighteenth-Century Amsterdam - Koudijs, Peter (Journal of Political Economy, 2015)
This paper studies how private information is incorporated into prices, using a unique setting from the eighteenth century that is closer to stylized models of price discovery than modern-day markets. Specifically, the paper looks at English securities traded in both London and Amsterdam. Private information reached Amsterdam through sailing boats that sailed only twice a week and in adverse weather could not sail at all. Results are consistent with a Kyle model in which informed agents trade strategically. Most importantly, the speed of information revelation in Amsterdam depended on the expected time until the private signal would become public.